2017
DOI: 10.2106/jbjs.16.01386
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Topographic Anatomy Near the Femoral Head-Neck Perforation with Surgical Relevance

Abstract: The information is taken from normal hips and may not be directly applicable to the deformed hip. Nevertheless, it is a prerequisite for a surgeon to understand the normal anatomy and use those boundaries to prevent mistakes during intra-articular joint-preserving hip surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…A recent study established the safe margin of bone resection in the perforating area of retinacular vessels at a depth of 2.5 mm and 2 mm from the cartilage margin. 18 The same study also reported the anterior limit of the vascular synovial fold lying more anteriorly than initially thought. It is advisable to be cautious when performing bone resection from the 1 o'clock to 10 o'clock areas of the head-neck junction (►Fig.…”
Section: Surgical Techniquementioning
confidence: 73%
See 3 more Smart Citations
“…A recent study established the safe margin of bone resection in the perforating area of retinacular vessels at a depth of 2.5 mm and 2 mm from the cartilage margin. 18 The same study also reported the anterior limit of the vascular synovial fold lying more anteriorly than initially thought. It is advisable to be cautious when performing bone resection from the 1 o'clock to 10 o'clock areas of the head-neck junction (►Fig.…”
Section: Surgical Techniquementioning
confidence: 73%
“…26 With recent detailed knowledge of the vascular supply to the femoral head, resection of lateral cam deformities overlapping the vascular area is no longer an absolute isolated indication for open surgery. 17,18 The literature is very scarce concerning recommendations for the amount and shape of resection at the head-neck junction and acetabular margin. Few publications define the amount of safe bone resection on the femoral side before creating an increased risk of stress fracture, and there is no consensus about the depth and extension of resection.…”
Section: Fai Treatment: An Update Indications and Type Of Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…The rationale for head-preserving procedures is the desire to provide sufficient and long-lasting support to necrotic subchondral bone and cartilage [38] , in order to prevent collapse and subsequent osteoarthrosis of the joint. A tantalum rod was used to provide direct mechanical support [16] ; a bone graft was aimed to replace dead bone with viable bone [12][13][14] .…”
Section: Discussionmentioning
confidence: 99%